Primary Mesenteric Well-Differentiated Inflammatory Liposarcoma With Mucosal Extension: A Lesion With High Risk for Misdiagnosis - William Abel; Christopher J. Peterson; David P. Lebel; Douglas J. Grider (Case Reports in Surgery)
Well-differentiated liposarcomas are common retroperitoneal lesions, but exceedingly rare when primary to the small bowel mesentery, with only a handful of cases reported in the literature. Presented is a patient with a primary mesenteric well-differentiated inflammatory liposarcoma with mucosal extension at high risk for misdiagnosis. A broad differential diagnosis with careful histopathologic observation, ancillary immunohistochemical studies, and fluorescent in situ hybridization for MDM2 amplification are key to make a correct diagnosis. This is especially true if such a lesion was first noted in the lamina propria on histopathology from an endoscopic mucosal biopsy.